Teknik Konseling Individual Berwawasan Gender - Nadhifatuz Zulfa (UIN K.H. Abdurrahman Wahid Pekalongan, 2017)
Individual counseling techniques that are gender-sensitive, are individualized counseling techniques that are inserted by Gender Aware Counseling (GAC) techniques. That is, the counselor's assistance to the counselee (male and female), to increase gender awareness and sensitivity, broaden insights about gender roles, and help improve skills overcoming career development challenges in the background of gender relations. This technique includes, among others: attending behavior with gender insight, responding behavior, personalizing and initiating. GAC techniques that go into individual counseling techniques, among others: the conceptualisation of problems in responding, counseling interventions in personalizing, and termination after initiating. It is hoped that with this technique, able to solve problems based on gender equality, so that it will produce solutions that are gender sensitive